EFFECT OF WORK MOTIVATION AND ORGANIZATIONAL COMMITMENT ON TEACHERS’ PERFORMANCE WITH MODERATED BY ORGANIZATION CLIMATE IN STATE ELEMENTARY SCHOOL DISTRICT WINONG OF PATI REGENCY - Hery Sapuan, 12.5202.0250 (Jurnal Mahasiswa Pasca Sarjana, 2016)
This study aims to examine and analyze whether the effect of workmotivation and organizational commitment on teacher performance withorganizational climate as moderated variable in State Elementary School DistrictWinong of Pati regency.Sampling was done by purposive sampling method so that all teacherswho work in State Elementary School District Winong of Pati regency totaling158 as respondents. Mechanical testing of the data used in this study includetesting the validity of the factor analysis, reliability testing with Cronbach alphaformula, multiple regression analysis, and the significance test, the coefficient ofdetermination to prove the truth of the hypothesis of research and testingmoderation.The results showed that; work motivation has positive and significantimpact on teacher performance, organizational commitment has positive andsignificant effect on teacher performance, organizational climate has positive andsignificant impact on teacher performance, the effect of work motivation onteacher performance moderated by organizational climate, and the influence oforganizational commitment on teacher performance moderated by organizationalclimate at State Elementary School District Winong of Pati regency.Keywords: work motivation, organizational commitment, organizational climate, teacher performance